Validity of serum Toll-like receptor-2 (TLR-2) in women with breast tumor - Al-Ammiri, Hind H.; Al-Derzi, Aida R. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Toll-like receptor -2 (TLR-2)play important roles in tumor biology; by activation and promotion of tumor cell proliferation, resistance to apoptosis andalso, enhancement of tumor cell invasion and metastasis by regulating metalloproteinase and integrin’s.As toll-like receptors are widely expressed on tumor cells and participatein the initiation and progression of cancer, they may thus serve an important target and have an effective perspective on breast cancer treatment. Objectives:The aims of the present study was to determine the levels of TLR-2 in the sera of healthy people and patients with benign and malignant breast tumors and also to investigate the validity of using TLR-2 as specific diagnostic markers of breast cancer. It`sdetection at early stage of disease could identify those patients with a high risk of progression to aggressive cancers. Patients and methods:Thirty breast cancer femaleswith age range from 27-76 years were included in this study and they were among patients who attending the National Center For Early Detection Of Cancer - medical city complex / Ministry of Health,during the period from October 2011 to February 2012.Thirty clinically diagnosed patients with benign fibro adenoma and twenty apparently healthy women were chosen as a case control and healthy control groups respectively. For all these study groups, serum level of TLR-2 using sandwich ELISA technique was carried out. Results:There was a statically significant difference in the serum level of TLR-2in blood of breast cancer patients and case control group in comparison to healthy controls (p >0.001),however there was no significant differences in such a level between the first two groups (p=0.44); therefore we were dealing with breast tumor cases in general regarding serum TLR-2.By using Receiver operating characteristic curve (ROC) area, in order to study the validity value of serum Toll like receptor-2 in differentiated breast tumor patients from healthy controls, serum TLR-2has the highest area under the curve (0.930) with cut off value associated with highest (perfect) sensitivity (100%) was equal to or above 0.14ng/ml. Conclusion:The current study showed that serum levels of TLR-2were significantly higher in patients with benign and malignant breast tumors which may confirm a possible role of this marker in the pathogenesis of the disease, furthermore the best sensitivity and highest accuracy obtained from serum toll-like receptor-2 was by using a cut off values equal to or above 0.14ng/ml; Therefore, TLR-2 may be promising new diagnostic tools especially at early stages and among patients at high risk.